LncRNA HULC induces the progression of osteosarcoma by regulating the miR-372-3p/HMGB1 signalling axis - Yong Li; Jing-Jing Liu; Jia-Hui Zhou; Rui Chen; Chao-Qun Cen (BMC, 2020)
Abstract Background Osteosarcoma is a malignancy that normally affects children, adolescents, and young adults. Although accumulating evidence has demonstrated the importance of HULC in osteosarcoma, little is reported about its functional roles and molecular mechanisms. Methods The expression of HULC and miR-372-3p in osteosarcoma tissues was quantified by qRT-PCR. The regulatory roles of HULC and miR-372-3p on cell proliferation, apoptosis, migration and invasion were determined by CCK-8, colony formation, flow cytometry, wound healing, and transwell assays, respectively. The bioinformatics prediction software RAID v2.0 was used to predict the putative binding sites. The interactions among HULC, miR-372-3p and HMGB1 were explored by luciferase assay and western blot assay. Results Our results revealed elevated HULC and decreased miR-372-3p expression in both osteosarcoma tissues and cell lines. Overexpression of HULC or knockdown of miR-372-3p promoted osteosarcoma cell proliferation, migration and invasion and induced cell apoptosis. Bioinformatics and luciferase assays verified that HULC directly interacted with miR-372-3p to attenuate miR-372-3p binding to the HMGB1 3'-UTR. Furthermore, mechanistic investigations confirmed that activation of the miR-372-3p/HMGB1 regulatory loop by knockdown of miR-372-3p or overexpression of HMGB1 reversed the in vitro roles of HULC in promoting osteosarcoma cell proliferation, migration and invasion. Conclusion Our study is the first to demonstrate that HULC may act as a ceRNA to modulate HMGB1 expression by competitively sponging miR-372-3p, leading to the regulation of osteosarcoma progression, which provides new insight into osteosarcoma diagnosis and treatment.